(3fcJ GdYHGOGJs - (3GdbGVj TeS GdOjf LYaQ Hf YHO GdHGYKs
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf cJGH GdWgGQI , HGH aQGFV GdhVhA s
(3BNQgG (B:s
(3hEf ENJGQ GdUjGe UGe YTQI GjGe hGddg CYde JeJ fcJ GdYHGOGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis